Diamagnetic Raman Optical Activity of Chlorine, Bromine, and Iodine Gases - Šebestík, Jaroslav; Kapitán, Josef; Pačes, Ondřej; Bouř, Petr (Angewandte Chemie (International ed. in English), 2016)
Magnetic Raman optical activity of gases provides unique information about their electric and magnetic properties. Magnetic Raman optical activity has recently been observed in a paramagnetic gas (Angew. Chem. Int. Ed. 2012, 51, 11058; Angew. Chem. 2012, 124, 11220). In diamagnetic molecules, it has been considered too weak to be measurable. However, in chlorine, bromine and iodine vapors, we could detect a significant signal as well. Zeeman splitting of electronic ground-state energy levels cannot rationalize the observed circular intensity difference (CID) values of about 10(-4). These are explicable by participation of paramagnetic excited electronic states. Then a simple model including one electronic excited state provides reasonable spectral intensities. The results suggest that this kind of scattering by diamagnetic molecules is a general event observable under resonance conditions. The phenomenon sheds new light on the role of excited states in the Raman scattering, and may be used to probe molecular geometry and electronic structure.
Keywords: angular momentum theory; magnetic field; excited electronic states; Raman optical activity; diamagnetic molecules